PEMETAAN SARANA PERALATAN KHUSUS UNTUK PEMELIHARAAN BALAS PADA JALUR KERETA API DI INDONESIA: Mapping the Railway Maintenance Fleet for Ballast Maintenance in Indonesia - Dhaniswara, Aryadhatu; Muthohar, Imam; Sektiaji, Hutama (Spektrum Sipil, 2025)
Ballast maintenance is a crucial activity to ensure the reliability of railway tracks in Indonesia. This study aims to map the demand for special equipment required in ballast maintenance based on track length, maintenance frequency, and equipment productivity. The methodology involves calculating the average productivity of several types of ballast maintenance machines, such as tamping machines, ballast regulators & profiling, and ballast stabilization & consolidation, and comparing the results with the availability of equipment owned by the Directorate General of Railways, PT Kereta Api Indonesia, and private operators. The results indicate that although the availability of tamping machines is relatively sufficient, there is a significant shortage of ballast regulators & profiling as well as ballast stabilization machines across almost all railway networks in Indonesia. This shortage becomes more severe when only equipment manufactured after the year 2000 is considered, highlighting the need for additional procurement and redistribution of equipment to ensure optimal ballast maintenance.